Strain and Pressure Gauges from Tough, Conducting and Edible Hydrogels. Issue 1795 (2015) - Keller, Alex; Benz, Dominik; in het Panhuis, Marc
ABSTRACT: The development of highly conductive, robust edible hydrogels was investigated using a combination of the biopolymers gellan gum and gelatin, a common salt (NaCl) and plant-derived cross-linker (genipin). Robust strain gauge/pressure sensors were developed using edible materials to demonstrate the potential of these hydrogels. The hydrogels exhibited gauge factor and pressure sensitivity values of 7.6 ± 0.1 and 400 ± 7 μΩ/Pa for loads up to 3 kPa, respectively. Furthermore, these devices were able to operate under larger loads with gauge factor and pressure sensitivity values of 0.308 ± 0.002 and 7.17 ± 0.05 μΩ/Pa, respectively, for loads between 9 kPa and 280 kPa.